Central muscarinic cholinergic activation alters interaction between splenic dendritic cell and CD4+CD25- T cells in experimental colitis. - Peris Munyaka; Mohammad F Rabbi; Valentin A Pavlov; Kevin J Tracey; Ehsan Khafipour; Jean-Eric Ghia (PLoS ONE, 2014)
Background The cholinergic anti-inflammatory pathway (CAP) is based on vagus nerve (VN) activity that regulates macrophage and dendritic cell responses in the spleen through alpha-7 nicotinic acetylcholine receptor (a7nAChR) signaling. Inflammatory bowel disease (IBD) patients present dysautonomia with decreased vagus nerve activity, dendritic cell and T cell over-activation. The aim of this study was to investigate whether central activation of the CAP alters the function of dendritic cells (DCs) and sequential CD4+/CD25-T cell activation in the context of experimental colitis. Methods The dinitrobenzene sulfonic acid model of experimental colitis in C57BL/6 mice was used. Central, intracerebroventricular infusion of the M1 muscarinic acetylcholine receptor agonist McN-A-343 was used to activate CAP and vagus nerve and/or splenic nerve transection were performed. In addition, the role of α7nAChR signaling and the NF-kB pathway was studied. Serum amyloid protein (SAP)-A, colonic tissue cytokines, IL-12p70 and IL-23 in isolated splenic DCs, and cytokines levels in DC-CD4+CD25-T cell co-culture were determined. Results McN-A-343 treatment reduced colonic inflammation associated with decreased pro-inflammatory Th1/Th17 colonic and splenic cytokine secretion. Splenic DCs cytokine release was modulated through α7nAChR and the NF-kB signaling pathways. Cholinergic activation resulted in decreased CD4+CD25-T cell priming. The anti-inflammatory efficacy of central cholinergic activation was abolished in mice with vagotomy or splenic neurectomy. Conclusions Suppression of splenic immune cell activation and altered interaction between DCs and T cells are important aspects of the beneficial effect of brain activation of the CAP in experimental colitis. These findings may lead to improved therapeutic strategies in the treatment of IBD.